2012
DOI: 10.1111/j.1600-0501.2012.02557.x
|View full text |Cite
|
Sign up to set email alerts
|

Implant survival and complications. The Third EAO consensus conference 2012

Abstract: The consensus statements prepared by the group and later accepted at the plenary session as well as suggestions for future research are presented in this article. The four reviews by Jung et al., Pjetursson et al., Romeo & Storelli and Scheuber et al. are printed separately and present detailed analyses of the research topics.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
154
1
4

Year Published

2015
2015
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 179 publications
(161 citation statements)
references
References 4 publications
2
154
1
4
Order By: Relevance
“…1 Although many biomaterials (such as stainless steel and cobalt-chromium alloys) have been introduced into the clinical setting, titanium (Ti) continues to be considered the "gold standard" material for the elaboration of artificial implants mainly due to its highly biocompatible properties. 2,3 Ti dental implants have shown excellent survival rates in the past years, 4 however, the issue of bacterial colonization remains a problem as biofilm formation on the implant surface can lead to loss of osseointegration with subsequent treatment failure. [5][6][7] Thus, many chemical disinfection protocols have been developed to try and clean implants after surface infection, in hopes of avoiding surgical intervention and increase the survival rates of affected implants.…”
Section: Introductionmentioning
confidence: 99%
“…1 Although many biomaterials (such as stainless steel and cobalt-chromium alloys) have been introduced into the clinical setting, titanium (Ti) continues to be considered the "gold standard" material for the elaboration of artificial implants mainly due to its highly biocompatible properties. 2,3 Ti dental implants have shown excellent survival rates in the past years, 4 however, the issue of bacterial colonization remains a problem as biofilm formation on the implant surface can lead to loss of osseointegration with subsequent treatment failure. [5][6][7] Thus, many chemical disinfection protocols have been developed to try and clean implants after surface infection, in hopes of avoiding surgical intervention and increase the survival rates of affected implants.…”
Section: Introductionmentioning
confidence: 99%
“…For this reason, success rate cannot be the only variable considered when deciding whether to replace an endodontically treated tooth with an implant-generally speaking, preserving the tooth with the attached periodontal ligament is always the preferred method [16,17]. However, in order to replace a missing tooth, local and systemic conditions must allow for sufficient potential benefit to the patient; the best treatment option is an implant-attached prosthesis [18].…”
Section: Therapeutic Approach Indicationsmentioning
confidence: 99%
“…However, due to the lack of complications associated with prosthetic implants (e.g., tooth decay, endodontic treatment, and dental sensitivity) the number of long-term complications associated with a tooth-fixed prosthesis was higher than those associated with a implant-fixed prosthesis [20]. Additionally, Albrektss on et al (2012) found that technical complications occur more frequently with fixed prostheses than with single prostheses, thus proving that fixed prosthesis were safer [18].…”
Section: Therapeutic Approach Indicationsmentioning
confidence: 99%
See 1 more Smart Citation
“…Nie bez znaczenia pozostają także biologiczne skutki złego dopasowania prac protetycznych w postaci okołowszczepowych zapaleń tkanek miękkich (periimplant mucositis) i zaawansowanych stanów zapalnych z zanikiem tkanki kostnej (periimplantitis) czy w skrajnych przypadkach utraty wszczepu wraz z całą odbudową protetyczną. [14][15][16][17][18] Na końcowy efekt leczenia wpływ ma kilka zmiennych technicznych, np. : metoda wytwarzania modelu roboczego, technika wytwarzania metalowej czy ceramicznej suprastruktury i odbudowy ostatecznej, oraz fabryczna jakość dopasowania elementów implantologicznych względem siebie.…”
Section: Wstępunclassified